2002
DOI: 10.1177/135676670200800303
|View full text |Cite
|
Sign up to set email alerts
|

TV travel shows — A pre-taste of the destination

Abstract: This paper discusses what is communicated to the viewers through the content of TV travel shows. The concepts of destination image and travel motivation are focused on, and selected Swedish TV travel shows constitute the empirical basis for that discussion. The pictures could easily be used for many tourist destinations around the world — showing TV reporters and anonymous tourists taking part in various activities. However, the results indicate that the studied films are coloured by culture: not necessarily t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
3
31
0
2
Order By: Relevance
“…Information sources examined included professional advice (tour operators, travel agents, and airlines), word-of-mouth (friends, relatives, and social clubs), advertisement (print or broadcast media), and books, movies, or news (Baloglu & McCleary, 1999;Beerli & Martin, 2004a). Media, such as movies, guidebooks, and magazines, have been shown to play an important role in determining tourists' destination image because of their credibility and ability to reach a broad mass of potential tourists (Castelltort & Mader, 2010;Gartner & Shen, 1992;Hanefors & Mossberg, 2002;Kim & Richardson, 2003;Mercille, 2005;Pan, 2011).…”
Section: Information Sources For Destination Imagementioning
confidence: 99%
“…Information sources examined included professional advice (tour operators, travel agents, and airlines), word-of-mouth (friends, relatives, and social clubs), advertisement (print or broadcast media), and books, movies, or news (Baloglu & McCleary, 1999;Beerli & Martin, 2004a). Media, such as movies, guidebooks, and magazines, have been shown to play an important role in determining tourists' destination image because of their credibility and ability to reach a broad mass of potential tourists (Castelltort & Mader, 2010;Gartner & Shen, 1992;Hanefors & Mossberg, 2002;Kim & Richardson, 2003;Mercille, 2005;Pan, 2011).…”
Section: Information Sources For Destination Imagementioning
confidence: 99%
“…The commercial imperatives in a consumer culture are apparent in this field, with travel journalism being 'more about reporting on travel for entertainment and information purposes … it rarely includes investigative aspects' (Hanusch, 2010: 71). Many studies have found that travel journalism often stereotypes destinations (Cocking, 2009;Santos, 2004) and tends to focus on the presenter rather than the host culture (Dunn, 2005;Hanefors and Mossberg, 2002). More recently, a study of travel journalists found that consumer-driven roles were considered the most important, although there was also some support for being mediators between cultures, and, to a smaller extent, taking a critical view of travel (Hanusch, 2012b).…”
Section: Studying Lifestyle Journalismmentioning
confidence: 99%
“…Previous research has shown that different sources of information can project images in different ways (Akama & Kieti, 2003). Projected images have been examined in information sources such as tourism brochures (Hunter, 2012), tour operators (Grosspietsch, 2006), television travel shows (Hanefors & Mossberg, 2002;S. Pan et al, 2011), and travel magazines (Hsu & Song, 2012).…”
Section: Projected Imagementioning
confidence: 99%